(untitled) (Annals of Medical Research, 2022)
Aim: Hypocalcemia is the most common complication after thyroidectomy, and recurrent laryngeal nerve (RLN) injury is the most serious complication. In this study, we aimed to investigate the effect of intraoperative nerve monitor (IONM) use on postoperative RLN injury and hypocalcemia in a uniform low-variability group. Materials and Methods: Between April 2007 and December 2020, data of patients who underwent surgery due to benign thyroid disease were retrospectively analyzed. Patients under 18 and over 65 years of age, having no euthyroid status during surgery, and having neoplastic pathologies were excluded from the study. A total of 428 patients were included in the study and were divided into two groups. There were 313 patients in Group 1 (non-IONM group) and 115 patients in Group 2 (IONM group). The correlation of the use of IONM with postoperative RLN injury and hypocalcemia was analyzed. Results: There was no permanent vocal cord paralysis. Of the patients, transient vocal cord paresis was seen in 0.61%, transient hypocalcemia in 8.1%, and permanent hypocalcemia in 3.9%. There was no statistically significant difference between the groups regarding RLN injury; however, there was a significant difference in hypocalcemia between the groups (p=0,008). Conclusion: Our study results suggest that IONM use does not significantly reduce the risk of RLN injury, but decreases hypocalcemia, which is one of the most common complications of thyroid surgery, in patients with benign disease undergoing thyroid surgery. Further prospective studies in larger patient series are needed to investigate the IONM use considering pathological examination results, surgical techniques, and demographic data of patients.